The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/and.13111
|View full text |Cite
|
Sign up to set email alerts
|

The use of aniline blue chromatin condensation test on prediction of pregnancy in mild male factor and unexplained male infertility

Abstract: The aim of this study was to investigate the possibility of using sperm function tests (hypoosmotic swelling test [HOS], aniline blue [AB] staining test, and sperm chromatin dispersion [SCD]) to predict intrauterine insemination [IUI] success rate. A total of 243 couples with mild male factor or unexplained male infertility who underwent IUI were evaluated prospectively. The results of basic sperm analysis and sperm function tests were compared between pregnant or nonpregnant groups. The HOS (11.9 ± 9.6% vs. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Previous studies showed that physiopathological conditions such as varicocele may lead to a decreased sperm protamination (Irez et al, 2018;Talebi et al, 2008) and that an altered P1/P2 ratio increases the presence of immature sperm cells and sperm DNA damage, leading to infertility (Castillo et al, 2011;García-Peiró et al, 2011;Torregrosa et al, 2006 (Nasr-Esfahani et al, 2005;Tarozzi et al, 2009). Then, the evidence presented here shows that CMA3 test would be a suitable diagnostic test for male factor related to a lack of pregnancy and miscarriage risk.…”
Section: Clinical Significance Of Dna Condensationmentioning
confidence: 54%
See 1 more Smart Citation
“…Previous studies showed that physiopathological conditions such as varicocele may lead to a decreased sperm protamination (Irez et al, 2018;Talebi et al, 2008) and that an altered P1/P2 ratio increases the presence of immature sperm cells and sperm DNA damage, leading to infertility (Castillo et al, 2011;García-Peiró et al, 2011;Torregrosa et al, 2006 (Nasr-Esfahani et al, 2005;Tarozzi et al, 2009). Then, the evidence presented here shows that CMA3 test would be a suitable diagnostic test for male factor related to a lack of pregnancy and miscarriage risk.…”
Section: Clinical Significance Of Dna Condensationmentioning
confidence: 54%
“…While infertility is present in between 7% and 15% of couples in reproductive age, a male factor is present in half of the infertile couples (Louis et al, 2013; WHO, 2010). Sperm cell provides the male genome complement, but studies in the last decade show that it also provides important epigenetic signals (Krausz et al, 2015; Sharma et al, 2019), crucial nRNAs necessary for the first stages of embryogenesis and the centriole that will be used in zygote development (Fishman et al, 2018; Giacone et al, 2019; Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We straightened this multiple regression analysis results by ROC curve that permitted us to find an AB test cut-off of 19% predictive for sperm count and motility, but not for morphology. Whereas several authors found an AB test cut-off in relation with clinical results [26,41], we identified a cut-off value in relation to semen parameters was considered to be significant data showed a correlation between a positive AB test and impaired sperm parameters: poorly packed sperm chromatin makes DNA more susceptible to reactive oxygen species (ROS) attack [16]. Oxidative stress condition has a negative effect both on mitochondrial functionality and DNA: this leads to a decrease in sperm motility and an impairment of DNA integrity [53].…”
Section: Discussionmentioning
confidence: 99%
“…On the day of insemination, all subjects underwent semen analysis: fresh semen was collected in a sterile jar by masturbation after 3-5 days of sexual abstinence. Semen analysis has been performed following the WHO 2010 [28] at 5° percentile: semen volume, 1,5 (1,4-1,7) ml; total sperm number, 39 (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) million per ejaculate, sperm concentration, 15 (12-16) million per ml; progressive motility, 32% (31)(32)(33)(34); total (progressive, non-progressive) motility, 40% (38)(39)(40)(41)(42); morphology 4,0% (3,0-4,0). Swim-up was performed for semen preparation.…”
Section: Semen Assessment and Preparationmentioning
confidence: 99%
“…Histone content assay using aniline blue staining was carried out to assess the nuclear maturity status of the spermatozoa. Slides were prepared by smearing raw specimen, air-drying, and fixing in 4% paraformaldehyde solution for 10 min, and then staining for 5 min in 5% aqueous aniline blue solution (pH 3.5) [ 28 , 29 ]. Spermatozoa were analyzed under bright-field illumination at 1000× magnification.…”
Section: Methodsmentioning
confidence: 99%